On the convergence rates of Gladyshev’s Hurst index estimator - Kubilius, K.; Melichov, D. (Nonlinear Analysis: Modelling and Control, 2010)
This paper presents the convergence rates for a modified Gladyshev’s estimator of the Hurst index of the fractional Brownian motion.